The Project-Based Learning Model Improves Ability to Understand Environmental Cleanliness in Early Childhood - Ayu Aprilia Pangestu Putri Putri; Budi Rahardjo; Nur Amalia Olby (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
An understanding of environmental cleanliness is an important element in achieving early childhood learning related to the habituation of clean and healthy living behavior (PHBS), one of the elements of early childhood development assessment, namely the element of identity in the implementation of the independent curriculum. This study aims to analyze the project-based learning model on the ability to understand environmental hygiene in children aged 5-6 years in Kindergarten. This type of research is quantitative. The experimental method with a one-group pretest-posttest design was used in this study. The sample is 38 children. Data collection techniques through observation with assessment instruments. Data analysis techniques using descriptive qualitative analysis, quantitative and inferential statistics. The study results are that the project-based learning model significantly affects the ability to understand environmental hygiene in early childhood by creating quality interactions between teachers and children and increasing thinking skills (Higher Order Thinking Skills- HOTS). The ability to understand is included in HOTS, while data on the ability to understand cleanliness related to Clean Healthy Lifestyle (PHBS) collected include; the child's ability to understand the cleanliness of the room/toilet/latrine; do not litter; understand self-protection from mosquito larvae, the importance of planting trees in creating clean air; and cleanliness of the gutters around the child's environment.